The Influence of Transformational Leadership, Digital Technology and Knowledge Sharing on Corporate Sustainability Performance Mediated by Organizational Innovation Performance - Wanda Rahma; Dita Oki Berliyanti; Eleonora Sofilda; Budi Santosa (Cv. Syntax Corporation Indonesia, 2026)
This study aims to examine the relationship between Transformational Leadership, Digital Technology, and Knowledge Sharing on Corporate Sustainability Performance mediated by Organizational Innovation Performance. The research data was taken from two energy companies, namely PT Adaro Energy Indonesia Tbk (Adaro) and PT Medco Energi Internasional Tbk (Medco). Sampling used Google Form in distributing the questionnaire. This study uses a quantitative approach through sampling with Purposive Sampling, the data analysis method used Structural Equation Model (SEM) using SmartPLS. The results of this study indicate that Transformational Leadership has proven to have no positive effect on Corporate Sustainability Performance. Digital Technology has proven to have a positive effect on Corporate Sustainability Performance. Knowledge Sharing has not proven to have a positive effect on Corporate Sustainability Performance. Transformational Leadership has proven to have a positive effect on Organizational Innovation Performance. Digital Technology has proven to have no positive effect on Organizational Innovation Performance. Knowledge Sharing has proven to have a positive effect on Organizational Innovation Performance. Organizational Innovation Performance has proven to have a positive effect on Corporate Sustainability Performance. Organizational Innovation Performance has been shown to mediate the effect of Transformational Leadership on Corporate Sustainability Performance. Organizational Innovation Performance has not been shown to mediate the effect of Digital Technology on Corporate Sustainability Performance. Organizational Innovation Performance has been shown to mediate the effect of Knowledge Sharing on Corporate Sustainability Performance. The implication of Management should strengthen transformational leadership, strategically integrate digital technology, create effective knowledge-sharing systems, and promote sustainable innovation through incentives and regular performance measurement.